Body measurements of Gadus morhua during Alkor cruise AL614 - Luisa Listmann (PANGAEA, 2025)
This data set includes single fish cod data collected during the RV ALKOR cruise AL614 cruise conducted in June 2024 (6th to 15th of June) in the Western Baltic Sea by the University of Hamburg. The cruise was part of the 5-year MARSYS teaching cruise program of the University of Hamburg GFP20-1_047. The cruises are designed to train students in sampling methods targeting the different compartments of a marine ecosystem. All single fish measurements were made directly on board. Full wet weights of cods were measured. Subsequently, cods were gutted and liver weights, gonad weights and sexes, gutted wet weights (i.e., gutted wet mass), gonad stages and liver nematode infestations were recorded.